Increased interleukin 12 production in progressive multiple sclerosis: Induction by activated CD4(+) T cells via CD40 ligand - Balashov, Konstantin E. (The National Academy of Sciences of the USA, 1997)
Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system postulated to be a cell-mediated autoimmune disease in which interferon γ (IFN-γ) plays an important role. There is increased IFN-γ secretion in MS, and IFN-γ administration induces exacerbations of disease. We found that interleukin 12 (IL-12) was responsible for raised IFN-γ secretion in MS as anti-IL-12 antibodies reversed raised anti-CD3-induced IFN-γ in MS patients to normal levels. Furthermore, we found a marked increase in T cell receptor-mediated IL-12 secretion in progressive MS patients vs. controls (24.8 ± 7.7 pg/ml vs. 1.5 ± 1.0 pg/ml, P = 0.003) and vs. relapsing–remitting patients (3.7 ± 1.4 pg/ml, P < 0.05). Investigation of the cellular basis for raised IL-12 demonstrated that T cells from MS patients induced IL-12 secretion from non-T cells, and that T cells from MS patients could even drive non-T cells from normal subjects to produce increased IL-12. Anti-CD40 ligand antibody completely blocked IL-12 secretion induced by activated T cells, and we found increased CD40 ligand expression by activated CD4(+) T cells in MS patients vs. controls. The CD40 ligand-dependent Th1-type immune activation was observed in the progressive but not in the relapsing–remitting form of MS, suggesting a link to disease pathogenesis and progression and providing a basis for immune intervention in the disease.